Identity negotiation processes among Black and Latinx sexual minority young adult mental health service users. Issue 1 (2nd January 2020) - Moore, Kiara L.; Camacho, David; Munson, Michelle R.
Abstract: The transition to adulthood presents particular challenges for Black and Latinx sexual minorities in need of mental health services. Identity formation and marginalization during this developmental period can interfere with help-seeking and lead to health disparities. Identity-specific psychosocial supports are needed to assist young adults to successfully navigate these challenges, but research on identity processes, help-seeking, and service-utilization among sexual minority young people of color is very limited. To better understand how multiple minority young people navigate their identities in the context of using, or choosing not to use, mental health services, this study qualitatively explored the experiences of 31 emerging adults. Through in-depth interviews, analyses revealed that young adults negotiated social identity norms about mental health help-seeking by separating from unhelpful norms, managing stigmatized aspects of identity, integrating helpful identity alternatives, and forming individualized perspectives on help-seeking that allowed them to maintain important connections to their minority group identities. Findings are discussed in relation to previous research on ethnic and sexual minority identity development and service utilization. Practice and research recommendations for increasing knowledge, improving help-seeking, and promoting resilience around young adults' intersectional identities are offered.